COMPREHENSIVE ASSESSMENT METHODS OF LAND RESOURCE USE EFFICIENCY (Scientific journal of the Fergana State University, 2024)
This article discusses the methods of comprehensive evaluation of the efficiency of land resource use. In addition, methods were proposed to reveal that a one-sided (technical-economic) approach to development in agriculture over the past years, assuming that it is achieved only by continuously expanding the use of land and water resources and material resources, causes environmental problems by evaluating 50-60 years of indicators.